Development of Stunting Early Detection Kit for Children under Two Years: Validity and Reliability - Nurlita, Aphrodite Nadya; Wigati, Maria; Hasanbasri, Mubasysyir; Jumarko, Jumarko; Helmyati, Siti (The Food and Nutrition Society of Indonesia in collaboration with the Department of Community Nutrition, IPB University, 2021)
This study aimed to determine validity and reliability of the new developed Stunting Early Detection Kit (SEDEK). This study was a cross-sectional study. A total sample of 30 children under two years from a Posyandu in Seyegan, Yogyakarta, was involved in the study. Every child was measured using SEDEK and infantometer-WHO Length for Age Growth Chart as the gold standard to find out its validity. Validity was determined by sensitivity, specificity, and predictive value. Reliability in this study was measured by intra-rater reliability, by comparing the first measurement and the second measurement from a rater using SEDEK. The intra-rater reliability determined using the Intraclass Correlation Coefficient (ICC). The results showed no significant difference between length measurements using SEDEK and the gold standards (p>0.05). The SEDEK sensitivity was 80%, specificity 85%, positive predictive value 72.7%, negative predictive value 89.5%. SEDEK reliability is demonstrated by ICC of 0.781. However, this study suggest that the current SEDEK version has not met the required sensitivity and positive predictivevalue of more than 80% so that it can be used as a detection tool. Further research is needed to improve the quality of SEDEK so that the SEDEK improved version can be used at the community-based health facilities level.